Metabolic impact of feeding prior to a 60-min bout of moderate-intensity exercise in females in a fasted state - Ratliff, Kayla M.; Kerksick, Chad M.; Moon, Jessica M.; Hagele, Anthony M.; Boring, Johnathan L.; Walden, Kylie; Gaige, Connor J.; Stecker, Richard A.; Sunderland, Kyle L.; Mumford, Petey W. (Frontiers in Sports and Active Living, 2023)
Background The metabolic impact of pre-exercise feeding of protein or carbohydrate on fat oxidation and energy expenditure rates, especially, in females, is poorly understood. Methods Recreationally active females (n = 15, 32 ± 10 years, 164.8 ± 5.6 cm, 63.5 ± 9.3 kg, 23.4 ± 3.2 kg/m2) completed four testing sessions in a randomized, double-blind, crossover fashion after fasting overnight. Participants ingested isovolumetric and isoenergetic solutions containing either 25 g of whey protein, casein protein, carbohydrate (CHO), or a non-caloric placebo (PLA). Participants then completed 60 min of treadmill exercise at 15% below ventilatory threshold 30 min after ingestion. Respiratory exchange ratio (RER) was evaluated throughout exercise and resting energy expenditure (REE) was assessed pre-exercise, and 0-, 60-, and 120-min post-exercise. Results A significant condition x time interaction was observed for RER (p = 0.008) during exercise, with CHO exhibiting higher RER values (vs. PLA) at four time points. A significant main effect for condition was observed for carbohydrate (p = 0.001) and fat (p = 0.02) oxidation rates during exercise, with fat oxidation rates being higher in PLA vs. CHO (p = 0.01). When total fat oxidized was calculated across the entire exercise bout, a significant main effect for condition was observed (p = 0.01), with PLA being greater than CHO (p = 0.04). A significant condition x time interaction (p = 0.02) was found for both absolute and normalized REE, with casein and whey protein having significantly higher values than CHO (p < 0.05) immediately post-exercise. Conclusion When compared to a fasted control (PLA), consuming CHO, but not protein, decreased total fat oxidation prior to a 60-min bout of moderate-intensity exercise in females.